2010
DOI: 10.2527/jas.2009-2152
|View full text |Cite
|
Sign up to set email alerts
|

Maternal selenium supplementation and timing of nutrient restriction in pregnant sheep: Effects on maternal endocrine status and placental characteristics1

Abstract: To determine the effects of maternal Se intake and plane of nutrition during midgestation, late gestation, or both on hormone and metabolite concentrations in the dam and on placental characteristics, pregnant ewe lambs (n = 64) were assigned to 1 of 8 treatments arranged in a 2 x 2 x 2 factorial array: Se level [initiated at breeding; adequate (3.05 microg/kg of BW) or high (70.4 microg/kg of BW)] and nutritional level [100% (control) or 60% (restricted) of NRC recommendations] fed at different times of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
2
24
1
3
Order By: Relevance
“…Asymmetric IUGR has been documented in several mammalian species including sheep (Jensen et al 1999, Anthony et al 2003, Lang et al 2003, swine (Widdowson 1971, Bauer et al 1998, guinea pigs (Saintonge & Rosso 1981), and humans (Pearce & Campbell 1985). As we believe that our nutritional restriction model is due to differences in placental function, independent of size (Lekatz et al 2010(Lekatz et al , 2011, basing offspring organ mass data per unit brain (i.e. a denominator that is consistent regardless of maternal nutritional intake) may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric IUGR has been documented in several mammalian species including sheep (Jensen et al 1999, Anthony et al 2003, Lang et al 2003, swine (Widdowson 1971, Bauer et al 1998, guinea pigs (Saintonge & Rosso 1981), and humans (Pearce & Campbell 1985). As we believe that our nutritional restriction model is due to differences in placental function, independent of size (Lekatz et al 2010(Lekatz et al , 2011, basing offspring organ mass data per unit brain (i.e. a denominator that is consistent regardless of maternal nutritional intake) may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Lamb serum samples were analyzed for cortisol concentration as described previously (Lekatz et al 2010). Briefly, serum samples (10 ml) were assayed in duplicate by the chemiluminescence immunoassay (Immulite 1000; Siemens, Los Angeles, CA, USA).…”
Section: Cortisol Analysismentioning
confidence: 99%
“…In this research model, nutritional plane during gestation has affected ewe endocrine profiles. Nutrient-restricted ewes had decreased IGF-I (Ward et al, 2008), progesterone Lekatz et al, 2010), and thyroid hormones (Ward et al, 2008;Lekatz et al, 2010), whereas ewes fed a high nutritional plane had decreased estradiol and progesterone but increased prolactin (Camacho et al, 2010) and cortisol during gestation. These alterations in hormones likely interact to play a role during the crucial mammary growth and development of gestation Banchero et al, 2006).…”
Section: Colostrum and Milk Productionmentioning
confidence: 99%
“…Maternal changes in body composition Carlson et al, 2009;Meyer et al, 2010b), endocrine and metabolic status (Ward et al, 2008;Lekatz et al, 2010), and colostrum yield and nutrient content (Swanson et al, 2008) have accompanied changes observed in offspring. Therefore, we hypothesized that gestational nutrition alters the subsequent milk production of the dam, even when nutrient requirements of lactation are met.…”
Section: Introductionmentioning
confidence: 99%
“…This information is novel and the mechanism for this is unknown. Perhaps increased concentrations of circulating Se in the offspring reduced the cellular proliferation of the secondary follicles, which has been observed in other tissue types (Tapiero et al, 2003;Carlson et al, 2009;Lekatz et al, 2010).…”
Section: Discussionmentioning
confidence: 93%